FEV1 and MRI ventilation defect reversibility in asthma and COPD. Issue 3 (26th March 2020) - Serajeddini, Hana; Eddy, Rachel L.; Licskai, Christopher; McCormack, David G.; Parraga, Grace
The underlying pathophysiological determinants of asthma and COPD are related in complex ways. Importantly however, post-bronchodilator forced expiratory volume in 1 s (FEV1 ) reversibility may occur in approximately 50% of COPD patients [1], whilst epidemiological [2] and magnetic resonance imaging (MRI) studies [3] suggest that, in asthma patients, FEV1 reversibility may diminish over time. As compared to patients with asthma or COPD alone, patients with co-existing asthma and COPD report worse clinical outcomes [4] and increased healthcare costs [5] and burden [4, 5]. MRI ventilation defect post-bronchodilator reversibility was not always concordant with FEV1 reversibility in asthma and COPD. MRI VDP may provide enhanced sensitivity to small airway response to inhaled medication. http://bit.ly/2qKnwID